2018
DOI: 10.1111/1467-9566.12803
|View full text |Cite
|
Sign up to set email alerts
|

Gender dynamics in the donation field: human tissue donation for research, therapy and feeding

Abstract: This paper examines how gender dynamics shape human tissue donation for research and for human health. Drawing on research investigating the donation of different types of bodily tissues including blood, plasma, breastmilk, cord blood, foetal tissue and placentae we consider how and why women and men are viewed as different kinds of donors. We situate these donation practices within a broader understanding of gender difference to explain why any sociology of donation needs to take account of gender. In so doin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…A recent sociological study of the gendered aspects of biological donations highlights a variety of cultural and social complexities that may influence willingness to participate in the donation of biological material. 47 The literature on blood donation also shows conflicting gender data. In the United Kingdom, in 2017, a study found that more women than men donated blood (56.6% vs. 43.4%).…”
Section: Discussionmentioning
confidence: 99%
“…A recent sociological study of the gendered aspects of biological donations highlights a variety of cultural and social complexities that may influence willingness to participate in the donation of biological material. 47 The literature on blood donation also shows conflicting gender data. In the United Kingdom, in 2017, a study found that more women than men donated blood (56.6% vs. 43.4%).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Waldby and colleagues 24 note female donors may be more strongly motivated than men by the connection they perceive they form with the recipient through donating, thus the salience of this may result in higher female donor return rates. In contrast, male donors may be more frequently marketed to and reminded to return, because of their known robustness to the donation procedure and the safety of the products they produce (e.g., recipient risk of Transfusion Related Acute Lung Injury 25 ) and these frequent reminders may prompt their higher return rate. 26, c.f.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy and birth continue to be romanticized as a broader cultural dynamic that shapes women's parenting responsibilities and makes difficult the refusal of a primary caregiving role (Lewis, 2018). Indicative of this, discussions of assistive reproductive technologies (in vitro fertilization, gamete donation and surrogacy) draw on a narrative of gifting to and caring for others that affirms rather than denies gendered understandings of care and of women's 'responsibility' towards others (Kent, Fannin, & Dowling, 2019). This means that even in instances where women donors are positioned as workers in the global fertility market, notions of love and self-sacrifice afford a low value to their bodily labour, preserving long-standing inequalities based in gender, class, race and global status (Schurr, 2018).…”
Section: Artificial Intelligence and Socially Aware Machinesmentioning
confidence: 99%